O16.4 Human Papillomavirus in Very Young Men Who Have Sex with Men and the Potential Benefit from Vaccination. (13th July 2013) - Zou, H; Morrow, A; Tabrizi, S; Grulich, A; Garland, S; Hocking, J; Bradshaw, C; Prestage, G; Fairley, C; Chen, M
Abstract : Background: Homosexually active men are at increased risk for human papillomavirus (HPV) infection and HPV associated anal cancer. Prophylactic HPV vaccines have maximum efficacy in people who have not already been infected with HPV. This study aims to determine the prevalence of HPV among teenage MSM. Methods: Same sex attracted males aged 16 to 20 were recruited in Melbourne via clinics, universities, community events, media, social networking and peer recruitment. At baseline, 3, 6, and 12 months anal and penile swabs and an oral rinse were obtained to test for 37 HPV genotypes. Results: 200 men were recruited. At baseline 39% had at least one type of HPV DNA detected from at least one site. High risk (HR), low risk (LR) and quadrivalent vaccine (QV) preventable types were detected in 31% (95% CI: 25–37%), 30% (95% CI: 24–37%) and 23% (95% CI: 17–29%) of men respectively. Multiple types of any, HR, LR and QV preventable HPV were detected in 27%, 13%, 11% and 8% of men respectively. The site specific prevalence of any HPV detected from the oral cavity, penis and anus were 2%, 9% and 31% respectively: the prevalence of QV preventable types at these 3 sites was 0.5%, 4% and 20% respectively. Anal HPV was absent in 27 of 30 men who reported never receiving anal sex. Additional results of serology for HPV 6/11/16 and 18 will also be presented. Conclusion: In this study, the first to focus on early HPV acquisition among teenage MSM, HPV was common but in the minority. HPV vaccination prior to the onset of sexual activity is ideal; however, short of universal vaccination of school aged males, selected vaccination of teenage same sex attracted young men could still prevent many infections.